Trends in Adolescent Suicide in Hong Kong for the Period 1980 to 2003 - Daniel T.L. Shek; Britta M. Lee; Joyce Chow (The Scientific World Journal)
This paper utilizes existing statistics on adolescent suicide to examine adolescent suicide trends and patterns in Hong Kong for the period 1980 to 2003. Several trends and patterns could be revealed from the analyses. First, there was a gradual rising trend where adolescent suicide rates in the 1990's and the early 2000's were higher than those in the 1980's. Second, suicide rates for adolescents aged 10-24 years were lower than those of other adult age groups. Third, although adolescent suicide rates in Hong Kong were lower than those reported in some English-speaking countries and Mainland China, the figures were higher than those reported in Taiwan. Fourth, suicide rates among teenagers in early adolescence were lower than those among adolescents in late adolescence. Fifth, although male adolescent suicide rates were in general higher than female adolescent suicide rates (10-24 age group), gender differences in suicide rates appeared to be moderated by age. Sixth, there was a gradual rising trend in adolescent proportional mortality rates for suicide since the 1990's. Seventh, proportional mortality rates for suicide among teenagers in early adolescence were lower than those among adolescents in late adolescence. Finally, although jumping from a height was a common method of adolescent suicide, there was a rising trend of using other methods, such as taking drugs, hanging and charcoal burning. The observed adolescent suicide phenomena are discussed in this study with reference to the socio-cultural context of Hong Kong.